2021
DOI: 10.1186/s12302-021-00530-x
|View full text |Cite
|
Sign up to set email alerts
|

Food web on ice: a pragmatic approach to investigate the trophic magnification of chemicals of concern

Abstract: Background The trophic magnification factor (TMF) is a metric that describes the average trophic magnification of a chemical through a food web. TMFs may be used for the risk assessment of chemicals, although TMFs for single compounds can vary considerably between studies despite thorough guidance available in the literature to eliminate potential sources of error. The practical realization of a TMF investigation is quite complex and often only a few chemicals can be investigated due to low sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Similarly, contradictory observations can also be found in the literature. In a comprehensive biomagnification study in a trophic network in a German lake, Kosfeld et al [ 46 ] found a positive log-linear relationship between C Lip of HOCs and the TL of fish. In contrast, Dufour et al [ 47 ] did not find a correlation between C Lip of HOCs and the TL of Arctic char ( Salvelinus alpinus ) in Lake Geneva, Switzerland.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, contradictory observations can also be found in the literature. In a comprehensive biomagnification study in a trophic network in a German lake, Kosfeld et al [ 46 ] found a positive log-linear relationship between C Lip of HOCs and the TL of fish. In contrast, Dufour et al [ 47 ] did not find a correlation between C Lip of HOCs and the TL of Arctic char ( Salvelinus alpinus ) in Lake Geneva, Switzerland.…”
Section: Resultsmentioning
confidence: 99%
“…This screening could support prioritisation [48] and decision-making processes for follow-up regulatory action for emerging compounds and chemical groups. c. To provide evidence to better understand and assess biomagnification processes of chemicals, for example using samples from selected food webs [49] and/or matched samples of predator and prey. d. To provide evidence on the occurrence of (bio)transformation products and typical chemical mixtures in top predators of different food webs, which can support advancements in risk modelling and assessment methods that are currently being developed with the ultimate goal to identify and manage hazardous chemicals more efficiently.…”
Section: Establish a European Research Infrastructure For The Use Of ...mentioning
confidence: 99%
“…Even if the model only represents reality in a simplified way, it can help to identify potentially bioaccumulative substances in a WoE approach. Supporting evidence could also come from existing biomonitoring studies in humans, mammals, and fish or newly generated data in approaches like "Food web on ice," which is a pragmatic approach to identifying the trophic magnification from historical data (Kosfeld et al, 2021). Monitoring studies have the advantage that they reveal directly what is happening in the environment.…”
Section: The Way Forwardmentioning
confidence: 99%